Work satisfaction and risk of burnout for endoscopy staff in Germany: Results of a nationwide survey - Adarkwah, Charles Christian; Labenz, Joachim; Birkner, Berndt; Beilenhoff, UIrike; Pfeifer, Ute; Hirsch, Oliver (Zeitschrift für Gastroenterologie, 2021)
Background Healthcare workers are facing ever-increasing challenges. Moreover, in many areas, there is a shortage of skilled personnel, so endoscopy staff are also increasingly exposed to the risk of developing burnout symptoms. Little is known about job satisfaction and burnout prevalence among endoscopy staff. The present study investigates the risk of burnout as well as job satisfaction among skilled personnel in German endoscopy units and practices.Methods An online survey was conducted among endoscopy staff, a significant proportion of whom are members of Deutsche Gesellschaft für Endoskopiefachberufe e. V. (DEGEA). In addition to general demographic variables, job satisfaction was determined by using the Short Questionnaire for the Assessment of General and Facet-Specific Job Satisfaction (KAFA), and the risk of burnout was determined by using the Maslach Burnout Inventory (MBI-D). Both were associated with structural characteristics.Results A representative sample took part in the survey (n = 674). The overall level of job satisfaction was high, with a rather elevated risk of burnout, although staff in executive positions performed better overall. Collegiality and mostly flat hierarchies are cited by the majority of those surveyed as positive aspects of their work. Nevertheless, 65 % describe their development opportunities as not performance-oriented, 20 % as virtually non-existent. Over 30 % of those surveyed consider their remuneration to be inadequate.Conclusion Representative data for the situation in German endoscopy units could be collected. Despite the fact that on average job satisfaction values are high, with a low risk of burnout, especially in comparison with other occupational groups, often mentioned critical aspects regarding the lack of development opportunities and non-performance-related payment should be taken seriously, and measures should be developed to avoid endangering endoscopy care in the long term.
Keywords: Work satisfaction; burnout; Maslach Burnout Inventory; endoscopy staff; survey